Meaning Negotiation and Linguistic Adaptation of Arabic Language Learners on Social Media - Very Erawanto; Jamila Wijayanti; Muhammad Farih (Darul Yasin Al Sys, 2026)
The advancement of digital technology has transformed communication practices, particularly through TikTok, which facilitates audio-visual synchronous discourse in contemporary digital interaction. This study aims to analyze patterns of Arabic language errors on TikTok and examine the linguistic dynamics that emerge within the digital communication ecosystem. A qualitative descriptive design with a digital ethnography approach was employed. Data were collected through non-participant observation of synchronous interactions on TikTok. The findings indicate that Arabic language errors, encompassing morphological, syntactic, lexical, and phonetic aspects, do not occur randomly but form systematic patterns influenced by Indonesian as the users’ native language, the demand for rapid digital communication, and the incorporation of dialectal forms through popular culture. The study further reveals that such errors should not be viewed solely as pathological linguistic phenomena but also as forms of linguistic adaptation and collaborative meaning negotiation. In digital spaces, language errors are frequently normalized by user communities as part of identity expression and communicative creativity. This study concludes that Arabic language errors on TikTok reflect the dynamic interaction between language structure, digital culture, and social identity formation. The findings contribute to digital linguistics and Arabic language pedagogy by emphasizing the need for more contextual language instruction and critical digital literacy, enabling users to distinguish between creative linguistic variation and structural language degradation.